MODERATING EFFECT OF FINANCIAL INNOVATIONS ON THE RELATIONSHIP BETWEEN MACROECONOMIC FACTORS AND FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN KENYA - MUTAI, NELLY CHELANGAT (Kabarak University, 2023)
Performance of commercial banks in Kenya have been declining since 2010 which was largely attributed to macro-economic factors, fiscal policies introduced by central bank of Kenya and market activities such as issuance of bonds and capping of interest rates, CBK 2018. However, whereas there is some theoretical literature on the effects of Macroeconomic factors on financial performance, little empirical evidence exists on these relationships particularly in Kenya. In addition, there has been increased integration due to embracement of financial innovations in the banking sector however the moderating effects of financial innovations on the relationship between macroeconomic factors and financial performance is still uncertain. The general objective of this study was to investigate the moderating effect of financial innovation on the effect of macroeconomic factors on financial performance of commercial banks in Kenya. Specific objectives of the study were; to investigate the effect of gross domestic product per capita, interest rates, inflation on financial performance of commercial banks and to access the moderating effect of financial innovations on the relationship. The study was anchored on four theories: Keynesian theory, Deflation theory, Interest rate parity theory and Constraint Induced Financial Innovation Theory. The study utilized secondary data for 10-year period as from 2011 to 2020. The target population of the study was 42 commercial banks that are licensed and supervised by the Central Bank of Kenya. Secondary panel data on financial performance of Commercial Banks was obtained from the individual institutions’ financial reports while data on macroeconomic factors was obtained from both Central Bank of Kenya and Kenya National Bureau of Statistics. The study found a significant and positive relationship (b=0.594, t=2.939, p=0.022) between GDP per capita and ROA but a significant and negative relationship (b= -0.430, t= -2.247, p=0.05) between inflation rate and ROA. The study found a moderating effect of interest rates on financial performance of commercial banks in Kenya (b= -5.292, t= -2,202, p=0.028). However, no moderating effect of financial innovations was found between either gross domestic product per capita or inflation on financial performance of the banks. This study concludes that when a bank’s innovations are at the highest, it can achieve a very high return on assets even when it keeps it interest rates very low. The study recommends that banks should implement the highest degree of financial innovations, which will enable them achieve very high return on assets even when they keep their interest rates very low.
Keywords: Financial Innovations; Macroeconomic factors; Financial Performance; Commercial Banks